2020
DOI: 10.3390/polym13010097
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Blended Asian Lacquers Using ToF–SIMS, Py–GC/MS and HPLC

Abstract: Asian lacquer is a special polymeric material tapped from lacquer trees. The tree’s sap is a complex mixture of compounds, such as catechol lipids, polysaccharides, glycoproteins, enzymes, and water. Researchers have not yet quantitatively analyzed blended lacquers. We evaluated the compositions of Japanese and Vietnamese lacquers, and blends of the two, using time-of-flight secondary ion mass spectrometry (ToF–SIMS), pyrolysis–gas chromatography/mass spectrometry (Py–GC/MS), and high-performance liquid chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The mixed lacquer sap was blended with turpentine oil with a volumetric ratio of 1:1 and coated on the Si wafer with a blade with approximately 10 µm thickness. The samples were then dried in a humidity-controlled chamber with 80% relative humidity at 22 • C for 2 h. The film-type samples were analyzed using positive and negative mode ToF-SIMS 5 (ION-TOF GmbH, Münster, Germany) with a base pressure of 4.0 × 10 −8 Pa [23]. The source was a pulsed 30 keV Bi 3 + beam, and the target current was maintained at 0.3 pA. A cycle time of 150 µs was used for the mass range of m/z 0-1870 and ion doses lower than 10 13 ions/cm 2 , which is the static SIMS limit.…”
Section: Time-of-flight Secondary Ion Mass Spectrometrymentioning
confidence: 99%
“…The mixed lacquer sap was blended with turpentine oil with a volumetric ratio of 1:1 and coated on the Si wafer with a blade with approximately 10 µm thickness. The samples were then dried in a humidity-controlled chamber with 80% relative humidity at 22 • C for 2 h. The film-type samples were analyzed using positive and negative mode ToF-SIMS 5 (ION-TOF GmbH, Münster, Germany) with a base pressure of 4.0 × 10 −8 Pa [23]. The source was a pulsed 30 keV Bi 3 + beam, and the target current was maintained at 0.3 pA. A cycle time of 150 µs was used for the mass range of m/z 0-1870 and ion doses lower than 10 13 ions/cm 2 , which is the static SIMS limit.…”
Section: Time-of-flight Secondary Ion Mass Spectrometrymentioning
confidence: 99%
“…To the best of our knowledge, this is the first attempt in the specific study of commercial alkyd paintings. Although some authors reported many problems in quantitation due to the pyrolytic procedure and pathways [32], or differences in the thicknesses of the samples taken from the paint surface [9], in the literature, there are also several studies on polymeric cultural heritage and industrial material where Py-GC/MS data is considered quantitatively [33][34][35]. To overcome reproducibility problems, the present study paid particular attention: (i) during the preparation of the samples to the thickness of the painted films (150 µm for all paint layers); (ii) during the sampling of the samples, to their weight, and (iii) during reaction with TMAH to the methylation efficiency.…”
Section: Thermally Assisted Hydrolysis and Methylation (Thm)-single S...mentioning
confidence: 99%
“…The hardened lacquer film is glossy, highly durable, chemical- and moisture-resistant, and insect repellent because of its complex molecular composition and limited solubility [ 16 , 17 , 18 , 19 ]. Previous studies have used various techniques to analyze lacquer sap and lacquered cultural heritage artifacts, such as pyrolysis-gas chromatography-mass spectrometry (Py-GC/MS) [ 18 , 19 , 20 ], surface analysis using time-of-flight secondary ion mass spectrometry (ToF-SIMS) [ 21 , 22 ], and X-ray photoelectron spectroscopy (XPS) [ 23 , 24 ] to understand the structural properties and composition of lacquer. However, few quantitative studies of mixed lacquer have been performed [ 20 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have used various techniques to analyze lacquer sap and lacquered cultural heritage artifacts, such as pyrolysis-gas chromatography-mass spectrometry (Py-GC/MS) [ 18 , 19 , 20 ], surface analysis using time-of-flight secondary ion mass spectrometry (ToF-SIMS) [ 21 , 22 ], and X-ray photoelectron spectroscopy (XPS) [ 23 , 24 ] to understand the structural properties and composition of lacquer. However, few quantitative studies of mixed lacquer have been performed [ 20 , 25 ]. In our previous study, the chemical structures of Korean, Chinese, and Vietnamese lacquer films and CNSL films were characterized using ToF-SIMS for the first time.…”
Section: Introductionmentioning
confidence: 99%